On the Concept of Creation in the Philosophy of Benedict Spinoza - Dymerets, Rostyslav (Sententiae, 2003)
Through the analysis of modes, man and the concept of intellectus in Spinoza’s philosophy, the author shows that creation is reduced to the concept of cognitive activity of intellectus. The essence of intellectus is to bridge the gap between the modality and substance of reality, and a specific, given modal possibility, expressed in desire, which signals the gap, manifested through affects. For Spinoza, creation shifts from the sphere of the will to the sphere of the action of intellectus. Thus, creation is a creative act that combines what should be and what is in reality. Therefore, every action of the intellect is presented as a modusof God. The author concludes that in Spinoza’s philosophy, God is an eternal creation of himself, an eternal self-modification through his modal states.